Rapid quantification of disaccharide isomers by derivatization in combination with ion mobility spectrometry in beer and milk - Ye, Keqi; Ye, Jiacheng; Yan, Yinghua; Ding, Chuan-Fan (Analyst (London), 2024)
The subtle structural variations among carbohydrate isomers pose significant challenges for their identification and quantification. Here, we propose a strategy for rapid identification and quantification of isomeric disaccharides via derivatization with 4-(3-methyl-5-oxo-pyrazolin-1-yl) benzoic acid (CPMP) and analysing by ion mobility spectrometry (IMS). After derivatization, the ionization efficiency of disaccharides was significantly improved. The disaccharide isomers were distinguished by determining the different ion mobilities of CPMP-labelled disaccharides. Among them, [M + 2CPMP + H] + was separated with a resolution of 1.484, almost achieving baseline separation. Subsequently, [M + CPMP + Na] + was used for the relative quantification of lactose and maltose, showing a good linear relationship with R 2 > 0.990. Finally, the method was successfully applied to the identification of lactose and maltose in beer and milk. The method is fast, accurate and effective for the identification of disaccharide isomers in complex samples. This work introduces rapid quantification of disaccharide isomers by derivatization in combination with ion mobility spectrometry in beer and milk.